(untitled) (CIPEEX, 2025)
This study analyzes abusive clauses in consumer contracts based on Chapter 36 (items 36.1 to 36.24) of Nunes Rizzatto’s Curso de Direito do Consumidor[1]. It examines the nature, legal characterization, and consequences of such clauses, which create significant imbalances in contractual relations by imposing excessive obligations or unfairly limiting consumer rights. Drawing on the Brazilian Consumer Defense Code (CDC), the research highlights the absolute nullity of abusive clauses, the importance of judicial oversight, and interpretative principles that strengthen consumer protection and contractual fairness. The findings show that abusive clauses undermine good faith and consumer autonomy, but the CDC provides effective mechanisms to restore balance. The study concludes that the CDC is a key instrument for ensuring justice and fairness in consumer relations by preventing and invalidating abusive contractual practices.